Upaya Meningkatkan Hasil Belajar PAI Materi Praktik Shalat dengan Metode Demonstrasi pada Siswa RA Al Misbah Kabupaten Ogan Ilir Provinsi Sumatera Selatan - Atpalina , Raudhatul; Tahta Sari H , Putri; Rabi’ah, Rabi’ah (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to improve students’ learning outcomes in the material of prayer in RA Al Misbah through the application of the demonstration method. This research uses the Classroom Action Research (CAR) model, which was carried out in two cycles. Each cycle consists of planning, action implementation, observation, and reflection. The results of the study indicate that in the first cycle, despite several obstacles such as students’ lack of attention and difficulty memorizing prayer recitations, significant improvement was observed in the second cycle with an increase in students’ learning completeness. This improvement is reflected in the test results, showing that more than 75% of students achieved scores above the Minimum Completion Criteria (KKM). The use of more effective learning media and increased student motivation also contributed to enhancing student engagement and understanding of prayer material. Based on these results, it can be concluded that the demonstration method is effective in improving students’ learning outcomes in prayer education.